Phonological Strategy Differences in Language Acquisition: A Comparative Study of Two Three-Year-Old Boys - Sarah Mudrika Zain; Erfan Muhamad Fauzi (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to identify the phonological differences shown by two three-year-old boys, namely Galfin Yasasi Habbika and Muhammad Arkhan Al Hafiz with different family backgrounds in Pangalengan, Bandung, and it analyzed the environmental factors and parental roles that contribute to variations in their phonological acquisition. This Study uses descriptive qualitative method with the data were conducted through video documentation of natural interactions and interviews with the parents of both children. The data collected were 18 utterances from each child which were then analyzed based on phonological aspects to identify error patterns, compensation strategies, and articulation skills. The findings showed that the two children has different phonological development patterns with Galfin showing more conservative phonological strategy by maintaining the original word structure, and people interaction environment from digital medias showing good phonological awarenees in Indonesian language development. While Arkhan showed more active phonological reconstruction by transforming difficult words into more easly produced form with a family environment that often made direct correction to Arkhan’s phonological errors which more stable and consistent phonological structure. Their phonological development was also successfully achieve through a variety of consistent support strategies that were responsive to the child’s emotional state and learning style. The result of this study support Chomsky’s Language Acquisition Device theory, in which both children demonstrated an innate capacity for language learning while showing how environmental triggers activated and shaped this biological predisposition because the children's ability to produce complex phonological structures without explicit instruction supports the nativist perspective on language acquisition.